A Spontaneous Emergence of Attachment Behavior in At‐Risk Children and a Correlation With Sensory Deficits. Issue 3 (10th July 2013) - Purvis, Karyn B.; McKenzie, L. Brooks; Cross, David R.; Razuri, Erin Becker
Abstract : Problem: Complex developmental trauma affects large numbers of children who have suffered from abuse, neglect, and/or deprivation. The effects often manifest in problems of attachment. Methods: Researchers conducted therapeutic day camps for at‐risk children to determine whether multimodal therapies could ameliorate the effects of complex developmental trauma . Two groups of adopted children (ages 3–9 and 10–14 years) with histories of trauma attended separate 3‐week camps. Findings: Data analysis indicated a positive correlation between negative attachment behaviors and deficits in sensory processing. Increased pro‐attachment behaviors were found to have a significant relationship with pre‐camp deficits in sensory processing. Conclusions: These results are discussed in the context of systems theory .